Relationship between emotional intelligence and quality of healthcare among nurses - Islam Oweidat; Mahmoud Alzoubi; Ghada Abu Shosha; Wafa’a Ta’an; Anas Khalifeh; Majdi M. Alzoubi; Khalid Al-Mugheed; Amany Anwar Saeed Alabdullah; Sally Mohammed Farghaly Abdelaliem (Frontiers in Psychology)
IntroductionHealthcare organizations worldwide face intense competition for survival in an ever-changing environment.ObjectivesThis study aims to examine the relationship between emotional intelligence (EI) and quality of healthcare (QHC) among Jordanian nurses working in governmental hospitals.MethodThis study was conducted using a descriptive correlational design and included a sample of 172 nurses. Participants from five governmental hospitals in Jordan completed online self-administered questionnaires, including the Nurse-Assessed Quality of Nursing Care Scale and the Genos Emotional Intelligence Concise Scale, along with sociodemographic data.ResultsThe participating nurses demonstrated a high level of EI (M = 3.809, SD ± 0.484) and a very high level of QHC (M = 4.260, SD ± 0.372). A statistically significant correlation was found between the total quality of healthcare variables and the total EI variable (r = 0.739, p < 0.01). Additionally, statistically significant correlations were observed between the QHC and EI, as well as their respective dimensions (r = 0.357–0.739). EI was found to be a significant predictor of the QHC (F = 34.872, p ≤ 0.001), with a positive correlation between the two variables (r = 0.733). EI accounted for 59.8% of the variation in the QHC.ConclusionEI is a key predictor of QHC. It plays an essential role in recruiting, staffing, promoting, and nurturing employees, making it a crucial criterion for achieving excellence in healthcare organizations.